UPAYA MENINGKATKAN HASIL BELAJAR PESERTA DIDIK DENGAN MENGGUNAKAN MODEL PEMBELAJARAN CONTEXTUAL TEACHING AND LEARNING (CTL) PADA MATA PELAJARAN ILMU PENGETAHUAN ALAM TENTANG MATERI CAHAYA DAN SIFAT-SIFATNYA DI KELAS V SD KATOLIK SANTO IGNATIUS MEDAN TAHUN - BUATON, HOTDIANA (Unversitas Katolik Santo Thomas, 2018)
This research is a Classroom Action Research (PTK) which aims to know theimplementation of learning and improve student learning outcomes by using theContextual Teaching and Learning (CTL) learning model in the subjects of NaturalSciences (IPA) with light matter and its properties in Class V SD Santo Catholic SantoIgnatius MedanLesson 2016-2017.Subjects in this study were the students of grade VSD Santo Catholic. Ignatius Medan Lessons Year 2016-2017 which amounted to 40people, consisting of 20 female students and 18 male students. The object of thisresearch is Classroom Action Research (PTK) by applying two cycles that are Cycle Iand Cycle II which includes planning, implementation, observation, and reflection. Theresults of this study indicate an increase in student learning outcomes in the subjects ofNatural Science (IPA) light material and the nature of class V SD Santo Catholic SantoIgnatius Medan. This is evident from the results of research conducted on the pretest ofstudents who got the complete value of 4 people or 10% while 36 students who did notcomplete or 90%. Then continued the research on the first cycle of students who got thecomplete value of 18 students or 45% while the students who did not complete as manyas 22 students or 55%, then there is an increase in the first cycle compared to thepreteSanto However, it has not met the completeness category that has been specified.Then proceeded on the second cycle of students who got a total score of 34 students or85% while students who are not complete as many as 6 students or 15%, then there is anincrease in cycle II compared to cycle I and has fulfilled the specified completeness.Furthermore, teacher activity on observation cycle I get an average of 58% and in cycleII has increased to 90%. While the activity of students on the learning process obtainedan average of 58% and in cycle II has increased to 81, 3%. Thus, it is concluded that byusing Contextual Teaching and Learning (CTL) learning model on Natural Sciencesubject (IPA) light material and its properties in class V SD Santo Ignatius Medan canimprove student learning outcomes. Therefore it is suggested for subsequent learning touse problem-based learning strategies so that student learning outcomes can increase.